Nonalcoholic Fatty Liver Disease Is Associated With Low Skeletal Muscle Mass in Overweight/Obese Youths - Pacifico, Lucia; Perla, Francesco Massimo; Andreoli, Gianmarco; Grieco, Rosangela; Pierimarchi, Pasquale; Chiesa, Claudio (Frontiers in Pediatrics, 2020)
Background: Recent studies in adult individuals have reported a link between nonalcoholic fatty liver disease (NAFLD) and sarcopenia. However, it is not known whether this relation would be found outside the adult population. Hence, we evaluated the relationship between NAFLD and skeletal muscle mass in children and adolescents with overweight/obesity. Methods: Two-hundred and thirty-four overweight/obese youths were enrolled. NAFLD was diagnosed by ultrasound examination, after exclusion of infectious and metabolic disorders. Forty of the children with NAFLD also underwent liver biopsy. Total and regional lean body mass and total fat mass were measured by dual-energy X-ray absorptiometry. The relative muscle mass (RMM) was expressed as the percentage of muscle mass (kg) relative to the sum of muscle and fat (kg) mass. Appendicular skeletal muscle mass (ASM) was calculated by sum of muscle mass in arms and legs (kg), and expressed as percentage of body weight. Results: Subjects were stratified according to tertiles of RMM. The prevalence of central obesity, dyslipidemia, insulin resistance, metabolic syndrome, NAFLD as well as nonalcoholic steatohepatitis (NASH) among children with biopsy-proven NAFLD was significantly increased in the lowest tertile of RMM. After adjustment for age, gender and pubertal status, children in the lowest tertile of RMM had a significantly higher risk for NAFLD (OR= 2.80, 95% CI=1.57-5.02) compared to those in the other two tertiles. This association persisted after additional adjustments (including central obesity, high blood pressure, elevated triglycerides, low high-density cholesterol lipoprotein, and insulin resistance). Similarly, the risk of NAFLD in the lowest tertile of ASM index was significantly higher compared to those in the other two tertiles after adjustment for the above confounders. Conclusions: This is the first study to establish a close and independent association between low muscle mass and NAFLD/NASH in overweight/obese youths. Considering the worldwide increase of pediatric obesity, measurements of muscle mass may serve as useful method of identifying among obese children those at high metabolic risk who may need intensive lifestyle interventions to prevent NAFLD and its progression.